The management of suspected or confirmed laryngopharyngeal reflux patients with recalcitrant symptoms: A contemporary review. (31st July 2019) - Lechien, Jerome R.; Muls, Vinciane; Dapri, Giovanni; Mouawad, François; Eisendrath, Pierre; Schindler, Antonio; Nacci, Andrea; Barillari, Maria R.; Finck, Camille; Saussez, Sven; Akst, Lee M.; Sataloff, Robert T.
Abstract: Objective: To summarise current knowledge about the prevalence, aetiology and management of recalcitrant laryngopharyngeal reflux (LPR) patients—those who do not respond to anti‐reflux medical treatment. Methods: A literature search was conducted following the PRISMA guidelines to identify studies that reported success of anti‐reflux medical treatment with emphasis on studies that attempted to be rigorous in defining a population of LPR patients and which subsequently explored the characteristics of non‐responder patients (ie aetiology of resistance; differential diagnoses; management and treatment). Three investigators screened publications for eligibility from PubMED, Cochrane Library and Scopus and excluded studies based on predetermined criteria. Design, diagnostic method, exclusion criteria, treatment characteristics, follow‐up and quality of outcome assessment were evaluated. Results: Of the 139 articles screened, 45 met the inclusion criteria. The definition of non‐responder patients varied substantially from one study to another and often did not include laryngopharyngeal signs. The reported success rate of conventional therapeutic trials ranged from 17% to 87% and depended on diagnostic criteria, treatment scheme, definition of treatment failure and treatment outcomes that varied substantially between studies. The management of non‐responders differed between studies with a few differential diagnoses reported. No study considered the profile of reflux (acidic, weakly acid, non‐acid or mixed) or addressed personalised treatment with the addition of alginate or magaldrate, low acid diet, or other interventions that have emerging evidence of efficacy. Conclusion: To date, there is no standardised management of LPR patients who do not respond to traditional treatment approached. A diagnostic and therapeutic algorithm is proposed to improve the management of these patients. Future studies will be necessary to confirm the efficacy of this algorithm through large cohort studies of non‐responder LPR patients. Level of evidence: 2a.